Automatic Quality of Service Control in Multi-core Systems using Cache Partitioning - Danielsson, Jakob; Seceleanu, Tiberiu; Jagemar, Marcus; Behnam, Moris; Sjodin, Mikael (2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA ), 2021)
In this paper, we present a last-level cache partitioning controller for multi-core systems. Our objective is to control the Quality of Service (QoS) of applications in multi-core systems by monitoring run-time performance and continuously re-sizing cache partition sizes according to the applications' needs. We discuss two different use-cases; one that promotes application fairness and another one that prioritizes applications according to the system engineers' desired execution behavior. We display the performance drawbacks of maintaining a fair schedule for all system tasks and its performance implications for system applications. We, therefore, implement a second control algorithm that enforces cache partition assignments according to user-defined priorities rather than system fairness. Our experiments reveal that it is possible, with non-instrusive (0.3-0.7% CPU utilization) cache controlling measures, to increase performance according to setpoints and maintain the QoS for specific applications in an over-saturated system.